Telavancin for the treatment of hospital-acquired pneumonia: findings from the ATTAIN studies. Issue 8 (August 2012) - Nannini, Esteban C; Corey, G Ralph; Stryjewski, Martin E
Treatment options for hospital-acquired pneumonia caused by Gram-positive organisms are far from ideal. The increase in vancomycin MICs among methicillin-resistant Staphylococcus aureus (MRSA) isolates, and the slow bactericidal action and poor lung penetration of vancomycin have driven the search for an alternative agent. Telavancin, a once-daily lipoglycopeptide, displays strong bactericidal activity against S. aureus . Two large Phase III randomized trials have recently compared intravenous telavancin (10mg/kg every 24 h) with vancomycin (1 g intravenously every 12 h) for 7–21 days for the treatment of hospital-acquired pneumonia caused by Gram positives. No significant differences were observed in the cure rates in the all-treated (n = 1503), the clinically evaluable (n = 654) and the microbiologically evaluable (n =480) populations. Telavancin performed better than vancomycin in patients with monomicrobial S. aureus pneumonia (84.2 vs 74.3%; 95% CI: 0.7–19.1), with MRSA (81.8 vs 74.1%; 95% CI: –3.5 to 19.3), and with strains having vancomycin MICs ≥1µg/ml (87.1 vs 74.3; 95% CI: 0.5–23). The rate of adverse events, including serious adverse events, was similar in both groups, with a slightly higher rate of serum creatinine increase in the telavancin-treated group. Based on these results, telavancin (already approved for this indication by the EMA) could certainly be added to the current treatment options, particularly in patients with MRSA pneumonia.